Analisis Perbandingan Return On Equity Ratio , Current Ratio, dan Debt to Equity Ratio pada PT Mayora Indah Tbk dan PT Indofood CBP Sukses Makmur Tbk Periode 2021-2024 - Okta Dwi Andhani; Dika Puspitaningrum (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
The purpose of this study is to analyze and compare the financial strength of PT Mayora Indah Tbk and PT Indofood CBP Sukses Makmur Tbk during the 2021–2024 period by using financial ratios, namely Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER). The research applies a descriptive comparative method with a quantitative approach, and the financial data were obtained from the (IDX). The results reveal that PT Mayora Indah Tbk has higher profitability and capital efficiency, as reflected by the increase in ROE and the DER value below 100%, which indicates a healthy capital structure and lower financial risk. Conversely, PT Indofood CBP Sukses Makmur Tbk demonstrates stronger liquidity, as shown by the continuous rise in CR each year, although the company still relies considerably on debt financing. Overall, PT Mayora Indah Tbk is considered more efficient in generating profits with controlled financial risk, while PT Indofood CBP Sukses Makmur Tbk excels in maintaining liquidity stability and meeting short-term obligations. The findings of this study are expected to provide added value for investors, management, and future researchers in assessing the financial health of companies within Indonesia’s (FMCG) sector.